Real-time velocity and mass flow rate measurement using infrared tomography [compact disc] - 404874 Pang, Jon Fea (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2004